(untitled) (Bangladesh Journal of Medical Science, 2026)
Background The prevalence of overweight and obesity is increasing due to sedentary lifestyles, with dental students particularly at risk due to prolonged sitting during study and clinical practice. This study examined the effects of interval training on body composition in overweight and obese dental students at Universiti Sains Malaysia (USM). Methodology Thirty-three participants classified as overweight (BMI 23.0– 27.5 kg/m²) or obese (BMI >27.5 kg/m²) were randomly assigned to either the control (n=17) or exercise (n=16) group. Body composition was assessed pre- and post-intervention, with baseline calorie intake recorded through a 24 h diet recall. The 12-week interval training programme was conducted three times per week, progressively increasing in duration every four weeks. Data were analysed to compare changes between and within groups. Results No significant differences were observed between the control and exercise groups in BMI (p=0.267), body fat percentage (BFP, p=0.957), lean mass (LM, p=0.746), resting metabolic rate (RMR, p=0.589), or waist-hip ratio (WHR, p=0.631) post-intervention. Similarly, within the exercise group, BMI (p=0.590), BFP (p=0.833), LM (p=0.944), RMR (p=0.584), and WHR (p=0.384) remained unchanged. Conclusion: The 12-week interval training did not significantly impact body composition parameters, likely due to the moderate exercise intensity, short duration, and lack of dietary control. Future studies should integrate structured dietary monitoring to enhance weight management outcomes. BJMS, Vol. 25 No. 02 April’26 Page: 539-547